Permainan Gobak Sodor terhadap Penggunaan Gadget pada Anak Usia 7-12 tahun - Widyasih Sunaringtyas; Linda (STIKES dan AKZI Karya Husada Kediri, 2022)
Gobak Sodor game is an interactive game that can overcome gadget addiction behavior in children. The duration and intensity of excessive use of gadgets can have a negative impact on children, so a substitute game is needed that can distract children from using gadgets, namely the game of gobak sodor. The purpose of this study was to analyze the game gobak sodor on the use of gadgets in children aged 7-12 years. The research design used a pre-experimental design with 31 samples using random sampling technique, data were collected by interview and analyzed using the Wilcoxon test. The results of the study before being given the intervention showed that most of the respondents (51.6%) were in the high category, after the intervention, almost half of the respondents (48.4%) were in the medium category. Statistical test results with Wilcoxon signed p-value = 0.00 <0.05, it means that there is an effect of the Gobak Sodor game on the use of gadgets. The gobak sodor game can involve physical activity, with physical activity distracting children from gadgets. So that if children play gobak sodor more often, the use of gadgets will be lower. For children, it is expected to make gobak sodor as an alternative game as a substitute for gadget games.